Reading Comprehension Strategies and Comprehension Level of Proficient and Low Proficient ESL Readers - Danga, Hawa Abdullai Morjan (1999)
This study is both quantitative and qualitative in nature. The study focuses on the use of reading comprehension strategies and comprehension level of proficient and low proficient ESL readers in the TESL Matriculation programme of Universiti Putra Malaysia (UPM). The think-aloud technique was used to investigate the use of reading comprehension strategies. The product of reading (comprehension level) was assessed by the means of oral retelling. The findings illustrate that both groups of readers depended much on bottom-up text processing, especially the low proficient ESL readers. The proficient ESL readers however, used significantly more metacognitive and top-down strategies than the low proficient ESL readers. The findings of this study further indicate that the proficient ESL readers tended to use more bottom-up strategies than the low proficient ESL readers. This contradicts findings of previous studies which illustrated that the low proficient ESL readers used more bottom-up strategies than the proficient ESL readers. However, this difference is attributable to the lack of competence in L2 among the low proficient ESL readers. This made them unable to report their thoughts frequently hence perhaps producing bottom-up strategies less than the proficient ESL readers. The findings also illustrate that the proficient ESL readers had a significantly higher level of comprehension than the low proficient ESL readers. The results of the qualitative analysis of think-aloud protocols suggest that the major problem faced by the ESL readers of this study seems to be their inadequate control over grammar and vocabulary in English. This also hindered the subjects' comprehension of the text especially among the low proficient ESL readers. Thus in order to derive meaning from the text, the ESL readers relied on bottom-up strategies. The results of the study also suggest that there is a need to enhance the students' linguistic knowledge in vocabulary and grammar of English as a second language to improve the students' efficient use of the reading strategies.